Impact of anxiety and tourists’ habits on their intention to vacation during and after the COVID-19 pandemic: Treatment effect analysis - Souissi, Amel; Cheffou, Abdoulkarim Idi; Said, Foued Ben (Journal of Tourism Management Research, 2023)
This research aims to examine how tourists’ anxiety, fear, and travel habits influenced their travel intentions to Switzerland after the first wave of the COVID-19 pandemic and the relaxation of containment measures. This study uses the endogenous treatment effect method to analyze the impact of travel habits and fear on travel intentions, surveying 1042 travelers from Western Europe, India, the United States, and Switzerland and applying the two-stage least squares (2SLS) technique. The findings indicate that non-anxious tourists visiting rural areas and usually on short to medium-duration vacations were highly willing to travel. Anxious tourists who had previously traveled to ski resorts also expressed willingness to travel after the COVID-19 pandemic. In addition, non-anxious tourists typically making individual travel arrangements had greater intent to travel. This analysis suggests that positive past travel experiences increase the desire to travel despite negative factors like health risks and social distancing constraints, and the primary motivation for travel is to engage in outdoor activities as a response to confinement These results are important for travel agencies as they can leverage them to target and encourage tourists with appropriate offers and targeted promotional campaigns.